Analysis of Chosen Behavioural Effects as a Driving Force of Altruism - Vojtech KONARIK; Ales MELECKY (Communications of International Proceedings, 2021)
We apply behavioural knowledge (anchoring, peer effect) on prosocial economic preferences. For this matter, data from a questionnaire that consists of 3 versions (basic, anchor, peer) are analysed by descriptive statistics and evaluated by using non-parametric statistical tests. The focus is on evaluation of the behavioural effects on the main variables (willingness to donate to the poor, the amount of the donation to a poor, willingness to donate a higher amount of money to a small child, the amount of the donation to a child) that are compared first within all versions and secondly between two selected versions. According to the results, no statistically significant effect of behavioural carries is present. This can be explained by weak setting of reaction to the behavioural stimuli.
Keywords: Altruism; Anchor; Economics; Empathy; Peer